Geochemistry and Petrogenesis of Dioritic-Gabbroic Pegmatites in the Bulfat Complex, Qala Diza, Northeastern Iraq (Iraqi National Journal of Earth Science (INJES), 2020)
2). Generally, the silica content in these pegmatites is from 46.70 wt. % to 52.67 wt. %.The relatively flat pattern of REEs is characterized by the slight enrichment of LREEs compared to HREEs indicating the common ancestry of the studied pegmatites. Also, the enrichment of these pegmatites in LILEs (Sr, Pb, Rb) and depletion in HFSEs especially (Nb, Ta, Y) indicate the environment of the island arcs. Moreover, the low ratios of (Rb/Sr)N and (Ba/Sr)N refer to that these pegmatites are derived from a basic origin.Tectonic discriminate diagrams show that the tectonic environment of studied pegmatites is I-type, which is the oceanic island arcs environment of sub alkaline rocks. The pegmatites of the present study have a genesis relationship with intrusions close to them in the study area; these intrusions are gabbros of Wadi Rashid that represent the environment of E-MORB. Moreover, the gabbros of Wadi Rashid and studied pegmatites are part of ophiolite-bearing terranes, they are found within upper allochthon thrust sheet. The current study of pegmatites reflects the oceanic island arcs environment, this indicates the existence of double island arcs, the first adjacent to the Arabian shelf, and the second close to the middle of paleo-ridge.Numerous evidences support that the gabbros of Wadi Rashid being as the likely parent to the studied pegmatites such as geochemistry, tectonogenesis, and the close spatial distribution of the pegmatites to the gabbros of Wadi Rashid. Moreover, the studied pegmatites appear to entail further dissection mainly due to the fact that the occurrence of dioritic- and gabbroic-pegmatites with a small-scale in the single intrusion might have its explanation in the liquid associated immiscibility.]]>
Keywords: Bulfat complex; Gabbroic pegmatite; Geochemistry; Petrogenesis